HLA-DRB1[asterisk]0102 is associated with TINU syndrome and bilateral, sudden-onset anterior uveitis but not with interstitial nephritis alone - Mackensen, Friederike; David, Felix; Schwenger, Vedat; Smith, L. K.; Rajalingam, R.; Levinson, R. D.; Austin, C. R.; Houghton, D.; Martin, T. M.; Rosenbaum, J. T. (British journal of ophthalmology, 2011)
Background Tubulointerstitial nephritis and uveitis (TINU) syndrome is a rare form of uveitis. Previously, the authors had demonstrated a strong association of human leukocyte antigen (HLA) DRB1*0102 with TINU. Here, the authors performed HLA analysis on subjects with isolated bilateral sudden-onset uveitis (as in the TINU subtype) or with isolated tubulointerstitial nephritis (TIN). - Methods Patients with sudden onset, anterior, bilateral uveitis not fulfilling a diagnosis of TINU were identified. Pathology reports were reviewed to identify subjects with biopsy-proven TIN. Molecular typing of the HLA-DRB1 gene was performed by the Luminex technology-based sequence-specific oligonucleotide (SSO) hybridisation method (One Lambda, Canoga Park, California). HLA-DRB1 allele frequencies were compared with normal published controls (http://www.ncbi.nlm.nih.gov/projects/gv/mhc/ihwg.cgi dbMHC Europe cohort) and the published TINU cohort (n=18). - Results The authors included 28 subjects with uveitis and 14 with TIN. There was a significantly higher frequency of DRB1*0102 in the isolated uveitis cohort versus in normal controls (10.7% vs 0.6%, respectively, p<0.0001; RR 14.3 (6.9-29.8)). None of the nephritis patients showed this HLA subtype. Another association with HLA-DRB1*08 was seen in the isolated uveitis cohort with an allele frequency of 10.7% versus 2.7% in normal controls (p=0.0019; RR 4.0 (1.8-9.0)). In contrast, the HLA-DRB1*08 was not different from controls in the TINU cohort (allele frequency 2.8%, p=not significant). - Conclusion The incidence of HLA-DRB1*0102 is increased in sudden-onset bilateral anterior uveitis, as seen in patients with TINU. The same allele does not appear to occur in increased frequency in patients with isolated TIN. HLA DRB1*0102 might predispose to this subset of uveitis.